THE ROLE AND FEATURES OF INVESTMENT IN ECONOMIC GROWTH - Bobokulov Sanjar , Bakhromkulovich (THE INNOVATION ECONOMY, 2025)
In this article, research was conducted aimed at highlighting the role and significance of investments in the country’s economic growth. The article also conducted research on the analysis of investments directed to our country, the dynamics of development and results. So, suggestions and recommendations on the role and significance of investments in ensuring economic growth.